Legal Protection of Third-Party Assets in Bankruptcy Disputes in Indonesia - Bakar, Ridwan (LEGAL BRIEF, 2024)
Bankruptcy in Indonesia often leads to legal issues related to the protection of third-party assets, especially when these assets are improperly included in the bankruptcy estate. This research aims to analyze the legal protection of third-party assets in bankruptcy disputes based on Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations, as well as the Civil Code. The research method used is normative juridical with a doctrinal approach, which examines legal norms through literature study and analysis of court decisions. The research results show that the Supreme Court consistently protects the legitimate property rights of third parties, excluding those assets from the bankruptcy estate unless there is strong evidence of their connection to the debtor's debts. This research reinforces the importance of careful verification by curators and the role of the courts in upholding justice and legal certainty in bankruptcy proceedings